Karakteristik Responden, Pekerjaan, Pendapatan dan Status Gizi pada Remaja - Chandra, Filius; Hatussaadah, Siti Fati; Fatmawati, Tina Yuli (Jurnal Akademika Baiturrahim Jambi, 2024)
Indonesian teenagers still of nutritional problems, namely thinness, fatness/obesity. Nutritional problems that often arise in adolescence can be caused by incorrect consumption patterns or an imbalance between consumption and recommended nutritional needs. This study aims to determine the characteristics of adolescents, employment and income of parents and the nutritional status of adolescents in SMP N Jambi City. Regency. The research design used is descriptive, using a cross sectional approach. The sample in this study were 74 students, the instruments used were questionnaires, microscopes and scales. Data were analyzed univariately. The research results showed that the largest age distribution of respondents was 14 years old (59.5%), the majority were female (54.1%), the majority of parents' jobs were laborers/farmers (62.2%), the majority of parents' income was less (58 .1%), and the majority had poor nutritional status (48.6%). It is recommended that teenagers pay attention to balanced nutritional intake in order to achieve good nutritional status.